The Influence of and Leadership Style Work Environment on Employee Performance At UPI Serang Campus - Firli Agusetiawan Shavab; Fuadi Fuadi; Rohman B (Journal of Applied Business, Taxation and Economics Research, 2021)
This research aims to analyze the influence of leadership styles and the work environment on employee performance at UPI Serang Campus. The research approach used is a mix method. The research population is an employee of education personnel at the University of Education Indonesia Kampus Serang, while the sample technique used in this study is purposive sampling using as many as 31 respondents. The method used is quantitative research. The data analysis methods used are decryptive statistical analysis, normality test, multicollinearity test, heteroskedasticity test, autocorrelation test, multiple linear regression test, and hypothesis test. The results of this study showed that: (1) leadership styles did not have a significant influence on employee performance. (2) The work environment has a significant influence on employee performance. (3) Leadership style and work environment have a significant influence on employee performance. The results of the coefficient of determination showed that the contribution of the influence of leadership style and the work environment on employee performance was 76.50%, while the remaining 22.50%, was a contribution from other variables (£) that were not examined in this study